Analysis of Total Phenolics, Flavonoids, and Antioxidant Activity of Cashew Leaf Extract (Anacardium occidentale L.) with Varying Ethanol Concentrations: Analisis Total Fenolik, Flavonoid, dan Aktivitas Antioksidan Ekstrak Daun Jambu Mete (Anacardium occidentale L.) dengan Variasi Konsentrasi Etanol - Kurniasari, Risma; Suzery, Meiny; Cahyono, Bambang (Universitas Andalas, 2024)
This study evaluated the effectiveness of various ethanol concentrations (50%, 70%, and 96%) in extracting bioactive compounds from cashew leaves (Anacardium occidentale). Parameters analyzed included total phenolics, total flavonoids, and antioxidant activity using the DPPH and H2O2 methods. The results showed that the 70% ethanol extract produced the highest total phenolic and flavonoid content as well as significant antioxidant activity compared to other ethanol concentrations. This study offers practical insights for pharmaceutical, cosmetic, and nutraceutical industries in selecting the optimal solvents for cashew leaf extraction. Additionally, the analysis showed that the 70% ethanol extract offered an optimal balance between extraction efficiency and antioxidant activity, making it the most efficient solvent for commercial use.